Three-dimensional Proton MR Spectroscopic Imaging of Premature and Term Neonates - Vigneron, Daniel B.; Barkovich, A. James; Noworolski, Susan M.; Bussche, Mary von dem; Henry, Roland G.; Lu, Ying; Partridge, J. Colin; Gregory, George; Ferriero, Donna M. (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: Previous studies have primarily used single-voxel techniques to obtain MR spectra from the neonatal brain. In this study, we applied 3D MR spectroscopic imaging techniques to detect the spatial distribution of MR spectroscopic imaging–detectable compounds in premature and term infants. The goals were to test the feasibility of obtaining 3D MR spectroscopic images of newborns, assess the spatial variations of metabolite levels, and determine age-dependent differences in MR spectroscopic imaging data.METHODS: MR spectroscopic imaging data were acquired from nine premature (postconceptional age, 30–34 weeks) and eight term (postconceptional age, 38–42 weeks) neonates, all with normal clinical and neurologic outcomes. A specialized point-resolved spectroscopy sequence with very selective saturation pulses was used to select a region encompassing the majority of the brain. Phase encoding in three dimensions was performed in a 17-minute acquisition time to obtain 3D spectral arrays with a 1.0 cm3 nominal spatial resolution.RESULTS: This study showed the feasibility of detecting the 3D distributions of choline, creatine, and N-acetylaspartate resonances in the neonatal brain. Significant spectral differences were detected among anatomic locations and between the premature and term groups.CONCLUSION: This initial study indicates that 3D MR spectroscopic imaging of the neonatal brain can detect anatomic and age-dependent variations in metabolite levels. This technique seems to be a powerful tool to assess the metabolic differences between anatomic regions and to follow the changes in cellular metabolites with brain maturation. This study also indicates the need for determining topologic and age-matched normative values before metabolic abnormalities in neonates can be accurately assessed by MR spectroscopy.